Reversible Inhibition of the In Vitro Coagulation of Human Plasma by Lectins - Freyssinet, J-M; Thevenon, D; Souque, A; Suscillon, M (Thrombosis and Haemostasis, 1982)
Wheat germ agglutinin (WGA) and concanavalin A (Con-A) (also red kidney bean agglutinin, PHA) have been found to be inhibitors of plasma clotting in vitro. At 40 µg/ml and 250 µg/ml (4.4 µM and 10 µM in carbohydrate binding sites, final concentrations) respectively, WGA and Con-A are able to double the activated partial thromboplastin time of normal human control plasma. Their inhibitory effect is due to their capacity to interact with the carbohydrate portion of blood clotting factors. It is totally abolished in the presence of specific saccharides for WGA or Con-A and is attenuated in the presence of 4% (v/v, final concentration) of human erythrocytes. The action of WGA is mediated by its ability to interact with N-acetylneuraminic acid. When purified phospholipid vesicles plus kaolin are used as an activator instead of cephalidin, this effect persists to the same extent. These two lectins also prolong the plasma clotting time using Russell's viper venom plus purified phospholipid vesicles as an activator. Quick's time was also prolonged by WGA and Con-A but to a lesser extent in this case. WGA can interact directly with some purified blood clotting factors (IX, X and II) in a classical lectin-glycoprotein precipitin reaction. When assessed at individual factors level in whole plasma using clotting assays, direct inhibitions by WGA are only apparent.
Keywords: Plasma coagulation; Reversible inhibition; Lectins